MANFAAT FORMULIR RESUME MEDIS BAGI PETUGAS BPJS DI RUMAH SAKIT IBU DAN ANAK ERIA BUNDA PEKANBARU - Jepisah, Doni; Anggraini, Gussri (Fakultas MIPA dan Kesehatan Universitas Muhammadiyah Riau, 2016)
The production process design is the form ones creativity in the form of a paper form or electronic form in the form of visual communication which has the function and aesthetic value to convey information or a message to everyone who has arranged the format so as to comply with certain requirements. Electronic form is a space that is displayed on the computer screen that is used to capture the data to be processed in an electronic data processing. The method used is descriptive qualitative approach is also called non statistik data processing. Data analysis techniques used in this research is the technique of inductive thinking process; that is to say, in testing hypotheses starts from the data collected and summarized, this technique is usually used to analyze the data obtained from observation and interviews Results showed Desai electronic form in the hospital sassy yellow pekanbaru not run well, hospitals are still using manual design, while at the present time other hospitals already use electronic medical records to facilitate the work, reductions loss of data and a double storage. The conclusion from this study that the factors that make hospitals sassy yellow pekanbaru not use an electronic medical record that there is no concern for the hospital to work in the system of medical records.